IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL DALAM MENUMBUHKAN SIKAP TOLERANSI DI SMPN 2 JOGOROTO - Siti Zulaikha; Didin Sirojudin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to describe the implementation of multicultural-based Islamic Religious Education (PAI) learning in fostering students’ tolerance at SMPN 2 Jogoroto. The research is grounded in the school’s need to develop learning that not only emphasizes cognitive understanding but also strengthens students’ awareness of diversity as part of character formation. A qualitative descriptive approach was used, with data collected through classroom observations, interviews with PAI teachers and students, and documentation analysis. The findings show that multicultural-based PAI learning is implemented through three main stages. In the planning stage, teachers integrate multicultural values into instructional documents. During implementation, teachers promote open dialogue, case discussions, heterogeneous group work, and respectful behavior. In the evaluation stage, assessment emphasizes both academic results and the development of students’ tolerance as observed in daily interactions. This implementation has been found to enhance students’ tolerance, reflected in their ability to accept differences, collaborate in diverse groups, and reduce potential conflicts. Thus, multicultural-based PAI learning plays an important role in strengthening a culture of tolerance within the school